Condensation Artifact. Issue 3 (23rd April 2021) - Zhou, Xiaohong Joe; Flannery, Michael P.; Ganin, Hagai; Karaman, M. Muge
Abstract : During the ongoing COVID‐19 pandemic, an artifact with hyperintense signal was observed on the brain images of a number of patients or research subjects, particularly those with heavy body weight and/or increased respiratory rate. The artifact was primarily seen on 3D or 2D sagittal or coronal T2‐weighted images, although it occasionally also appeared in the axial plane. It manifested as a bright spot or a cluster of bright spots at similar locations, superior or lateral superior to the skull. This artifact was found to be caused by condensed water droplet(s) in the head coil as a consequence of the altered moisture flow pattern associated with each exhalation due to the mask on the patient. We call this artifact condensation artifact. Several strategies have been proposed to prevent or resolve the artifact. Level of Evidence: 5 Technical Efficacy: Stage 1